The Transactional Distance Theory and Distance Learning Contexts: Theory Integration, Research Gaps, and Future Agenda - Hassan Abuhassna; Samer Alnawajha (MDPI AG, 2023)
Moore established transactional distance theory (TDT) to grasp transactional distance in the context of distance learning. Research using TDT in distance, open, and online learning environments has been undertaken. However, there are information gaps about what constitutes progress, future directions, and research deficits pertaining to TDT in the context of distance education. This systematic literature review (SLR) used PRISMA to analyze 42 papers to close the knowledge gap. Currently, TDT research in distance learning integrates various theories and models; nevertheless, there is a movement toward acceptance models and how to incorporate more relevant theories within the framework of distance learning. Future studies should integrate other aspects such as student motivation, student acceptance of technology, and student preparedness and desire to utilize technology in learning environments. As most research samples students, a research gap involving instructors and heterogeneous groups is proposed. It is projected that quantitative research will predominate in the future, leaving qualitative and mixed approaches as areas of investigation. This review illuminates the developments, future agenda, and research needs pertaining to TDT in the context of distance learning. It might serve as a foundation for future study on TDT in the context of distance, open, and online education.